2016
DOI: 10.1080/15583724.2016.1170701
|View full text |Cite
|
Sign up to set email alerts
|

Substituted Polyacetylenes: Synthesis, Properties, and Functions

Abstract: This perspective briefly introduces the status quo of various aspects of research on substituted polyacetylenes along with representative references. The research field of substituted polyacetylenes includes polymer design, polymer synthesis, polymer structure and properties, and polymer functions. Developments of well-defined catalysts and unique precision structures of polymers are challenging subjects in polymer design and synthesis. Elucidation of unique properties of substituted polyacetylenes has long dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 97 publications
0
37
0
Order By: Relevance
“…Chain-growth polymerization of alkynes with one ethynyl group per monomer molecule catalyzed by Rh-, W-, or Mo-based catalysts yielding the linear substituted polyacetylenes has been used for several decades. [28,29] The ethynyl groups of the monomer molecules are transformed into polyene (polyacetylene)-type conjugated main chains in this polymerization (see Scheme 1d epicting the polymerization of phenylacetylene to linear poly(phenylacetylene)). Recently,w e found that Rh I catalysts also polymerizedd iethynylarenes (diethynylbenzenes and 4,4'-diethynylbiphenyl), [24][25][26] and mixtures of diethynylarenes with monoethynylarenes.…”
Section: Preparation Of Microporouspolymer Networkdecorated With Termentioning
confidence: 99%
“…Chain-growth polymerization of alkynes with one ethynyl group per monomer molecule catalyzed by Rh-, W-, or Mo-based catalysts yielding the linear substituted polyacetylenes has been used for several decades. [28,29] The ethynyl groups of the monomer molecules are transformed into polyene (polyacetylene)-type conjugated main chains in this polymerization (see Scheme 1d epicting the polymerization of phenylacetylene to linear poly(phenylacetylene)). Recently,w e found that Rh I catalysts also polymerizedd iethynylarenes (diethynylbenzenes and 4,4'-diethynylbiphenyl), [24][25][26] and mixtures of diethynylarenes with monoethynylarenes.…”
Section: Preparation Of Microporouspolymer Networkdecorated With Termentioning
confidence: 99%
“…This technique is based on the chiral recognition ability of chiral stationary phases (CSPs) . In spite of polysaccharide‐based CSPs that showed good chiral separation abilities for varies of enantiomers, synthetic helical polymers, especially poly(phenylacetylene) derivatives, have also been widely investigated by researchers around the world because of their specific architectures …”
Section: Introductionmentioning
confidence: 99%
“…From scientific and applied approaches, this direction is perspective one. Therefore, the development of effective methods of polyacetylen compounds synthesis [5] based on available raw products is an actual task.…”
Section: Introductionmentioning
confidence: 99%